Two new species of Spiloxene (Hypoxidaceae) from the northwestern Cape, South Africa - D. A. Snijman (Bothalia: African Biodiversity & Conservation, 2006)
Newly described are two new species of Spiloxene Salisb.:  S. nana Snijman from the Bokkeveld Escarpment, Northern Cape Province, is a shade-loving plant with narrow, pale green leaves and small, white or rarely cream-coloured flowers; S. pusilla Snijman from the Matsikamma, Gifberg and Pakhuis Mountains. Western Cape Province, resembles S. nana in habit but the yellow- or white-tepalled flowers which are tetramerous or hexamerous have darkly coloured stamens and style and an ovary with a short, solid, narrow prolongation at the apex. Inhabiting rock overhangs formed by quartzitic sandstone sheets, both species are close allies of S. scullyi (Baker) Garside from Namaqualand.